Assortative mating, marital stability and the role of business cycles in the United States from 1968 to 2011 - Nikita Jacob (Journal of Applied Economics, 2024)
The strong negative correlation between divorce and a wide range of outcomes in terms of well-being, health, education and labour market performance has been well documented in the literature. Economic conditions have been found to affect marital stability. Shared gains from marriage also depend on spouses' characteristics such as age, education, ethnicity and religious beliefs. This paper examines the relationship between these spousal characteristics and the probability of dissolution while taking into account business cycle fluctuations. Using data from the Panel Study of Income Dynamics 1968-2011 for the United States and employing a duration modelling strategy, findings reveal that differences in educational attainment and ethnicity between spouses increase the hazard of marital dissolution. However similarity in religious beliefs and ethnicity reduce the risk of divorce. A period of economic growth improves marital stability. However, ethnic differences are a significant predictor of marital division, even in times of economic prosperity.
Keywords: 330; Assortative mating; business cycles; marital stability